Cutting Edge Research in Technologies - Volosencu, Constantin (IntechOpen, 2015)
The book Cutting Edge Research in Technologies responds to the great interest for innovation in the large domain of technologies. It presents contributions by researchers with high expertise in the field, serving as a valuable reference for scientists, researchers, graduate students, and professionals. The book has five chapters covering the following subjects: information and communication technologies and services with the aim of improving the quality of life and the mobility of users, localisation technologies for deployment of mobile robots in dynamic environments, embedded video processing circuit design flow in the Python language, data communications and networking, and textile weaving.